Analisis Hambatan Guru dan Dampaknya Terhadap Pemahaman Konsep Biologi Siswa SMA Negeri 1 Panai Hulu (Studi Kasus: Optimalisasi Penggunaan Alat Peraga) - Ardana, Ari; Hasibuan, Rosmidah; Harahap, Risma Delima (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyze the influence of teacher barriers and the optimization of teaching aids on students’ conceptual understanding of biology at SMA Negeri 1 Panai Hulu. This quantitative research employed a survey method using questionnaires administered to 140 students. The research instruments were validated and found to be reliable, with Cronbach’s Alpha values ranging from 0.845 to 0.900. Data were analyzed using multiple linear regression after meeting all classical assumption tests. The results indicate that teacher barriers have a significant effect on conceptual understanding (p = 0.017), while the optimization of teaching aids shows a stronger and highly significant effect (p = 0.000) with the highest beta value (β = 0.499). Simultaneously, both variables significantly influence students’ conceptual understanding, as reflected by an F-value of 14.866 and an R² value of 0.178, indicating that teacher barriers and teaching aids optimization explain 17.8% of the variance in students’ conceptual understanding. These findings emphasize the importance of improving teacher competence and optimizing the use of teaching aids as key strategies to enhance biology conceptual understanding in secondary education.